Inggris - Sinta Yuliana; Ratih Guswinda; Hanindya Fidela Ulayya; Nabilla Putri Auliyah Auliyah (Jurnal Farmasi Indonesia, 2026)
The Mentha spicata L., commonly known as spearmint, is a plant rich in essential oils (1.2% – 1.5%) with major compounds including myrcene, L-limonene, cis-dihydrocarvone, and L-carvone, which possess anti-inflammatory, antioxidant, and antifungal activities. This study aims to formulate a spearmint oil nanogel preparation to enhance the skin penetration of active substances and to evaluate the effect of varying HPMC concentrations (3%, 5%, and 7%) on the physical characteristics of the preparation and its percent transmittance value. The research was conducted experimentally. The characterization of the preparation included organoleptic tests, homogeneity, pH, viscosity, spreadability, adhesion capacity, and percent transmittance testing using UV-Vis spectrophotometry to measure the clarity of the nanoemulsion preparation. The results showed that the spearmint nanoemulsion had an average particle size of 9.6 nm with a percent transmittance value reaching 98.23%, indicating the formation of a clear nano-sized system. Variations in HPMC concentration had a significant effect on the physical properties of the gel; higher HPMC concentrations resulted in increased viscosity and adhesion capacity, while spreadability decreased. Formula III, containing 7% HPMC, was concluded to be the best formula as it met all the parameter requirements for the physical quality of an ideal gel preparation, including a skin-safe pH (6.42), stable viscosity (340 dPas), as well as spreadability and adhesion capacity consistent with the literature.